Frequencies of single-nucleotide polymorphisms and haplotypes of the SLCO1B1 gene in selected populations of the western balkans - A. Daka Grapci; A. Dimovski; A. Kapedanovska; M. Vavlukis; A. Eftimov; N. Matevska Geshkovska; N. Labachevski; K. Jakjovski; D. Goran; S. Kedev; K. Mladenovska (Walter de Gruyter GmbH, 2015)
As a membrane influx transporter, organic anion-transporting polypeptide 1B1 (OATP1B1) regulates the cellular uptake of a number of endogenous compounds and drugs. The aim of this study was to characterize the diversity of the solute carrier organic anion transporter family member 1B1 (SLCO1B1) gene encoding this transporter in two ethnic groups populating the Western Balkans. The distribution of SCLO1B1 alleles was determined at seven variant sites (c.388A>G, c.521T>C, c.571T>C, c.597C>T, c.1086C>T, c.1463G>C and c.*439T>G) in 266 Macedonians and 94 Albanians using the TaqMan allelic discrimination assay. No significant difference in the frequencies of the single nucleotide polymorphisms (SNPs) was observed between these populations. The frequency of the c.521T>C SNP was the lowest (<13.7 and 12.2%, respectively), while the frequencies of all other SNP alleles were above 40.0%. Variant alleles of c.1463G>C and c.1086 C>T SNPs were not identified in either ethnic group. The haplotype analysis revealed 20 and 21 different haplotypes in the Macedonian and Albanian population, respectively. The most common haplotype in both ethnic groups, *1J/*1K/*1L, had a frequency of 39.0% and 26.6%, respectively. In both populations, the variant alleles of the functionally significant c.521T>C and c.388A>G SNPs existed in one major haplotype (*15/*16/*17), with a frequency of 8.6 and 2.4% in the Macedonian and Albanian subjects, respectively. In conclusion, sequence variations of the SLCO1B1 gene in the studied populations occur at high frequencies, which are similar to that of the Caucasian population. Further studies are needed to evaluate the clinical significance of these SNPs and/ or the major SLCO1B1 haplotypes they form for a large number of substrates and for susceptibility to certain diseases.
Keywords: Haplotypes; organic anion-transporting polypeptide 1B1 (OATP1B1); single nucleotide polymorphisms (SNPs); Western Balkan populations; solute carrier organic anion-transporter family member 1B1 (SLCO1B1) gene